TAGMEMIK KENNET LEE PIKE DALAM NOVEL LEBIH SENYAP DARI BISIKAN KARYA ANDINA DWIFATMA - Khasanah, Uswatun; Yanuarsih, Sri; Letreng, I wayan (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
Tagmemic is a linguistic theory developed by Kennet Lee Pike and used to analyze language, culture, and meaning. This study aims to analyze, clarify, and describe broadly in the preparation of sentence meanings, understood by using the conceptual tool of tagmeme, which focuses on the ethical and emic aspects of meaning consisting of (1) Perspective is a point of view or a description, (2) Hierarchy began with the simplest arrangement, namely words used to make sentences, (3) Context is the form of language based on its origin, and (4) Units are connecting words between two structures; continuous and contradictory. Meanwhile, to understand the structure of sentences using tagmeme characteristics in the form of (1) Slots, (2) Classes, Roles, and (3) Cohesion. The subject is the novel "Lebih Senyap Dari Bisikan" by Andina Dwifatma. The method used is descriptive qualitative with a grammatical semantic approach. Data collection techniques are in the form of documentation studies or literature studies. Analysis techniques include: reading, marking, noting, checking, categorizing, compiling, analyzing, appreciating, interpreting, and concluding. The results of the study are to find out the form of sentence structure and understanding of meaning focusing on ethical characteristics related to understanding meaning from the author's point of view and emic characteristics referring to understanding meaning absorbed through the environment or surrounding within the scope of people's lives as well as affirming meaning in words or sentences based on the culture where the language originates.